PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KEDISIPLINAN GURU DI UPTD SD NEGERI MAULAFA - Kofi, Godelifa; Bernard Mbuik, Heryon; M. A. Hendrik, Hingrida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher discipline is one of the essential factors in improving the quality of education because it directly influences the effectiveness of the learning process. However, teacher discipline is often affected by the leadership style implemented by school principals. This study aimed to determine the effect of transformational leadership of the principal on teacher discipline at UPTD SD Negeri Maulafa. This research employed a quantitative approach using a causal associative design. The population consisted of 44 teachers, all of whom were selected as research respondents through total sampling. Data were collected using validated and reliable questionnaires. The collected data were analyzed using descriptive statistics, normality and linearity tests, simple linear regression analysis, t-test, F-test, and coefficient of determination (R²) with the assistance of SPSS version 22. The findings indicated that transformational leadership was categorized as very good with an average score of 77.66, while teacher discipline was also categorized as very good with an average score of 69.50. The regression analysis produced the equation Y = 23.336 + 0.599X, indicating a positive relationship between transformational leadership and teacher discipline. Hypothesis testing showed tcount = 2.871 > ttable = 2.018 with a significance value of 0.006 < 0.05, indicating that transformational leadership has a positive and significant effect on teacher discipline. Furthermore, the coefficient of determination (R²) was 0.164, meaning that transformational leadership contributed 16.4% to teacher discipline, while the remaining 83.6% was influenced by other variables outside this study.